Determining barriers and facilitators to engagement for families in a family-based, multicomponent healthy lifestyles intervention for children and adolescents: a qualitative study - Yvonne C Anderson; Paul L Hofman; Cervantée EK Wild; Ngauru T Rawiri; Esther J Willing (BMJ Open)
Objectives Recruitment and retention in child and adolescent healthy lifestyle intervention services for childhood obesity is challenging, and inequalities across social groups are persistent. This study aimed to understand the barriers and facilitators to engagement in a multicomponent assessment-and-intervention healthy lifestyle programme for children and their families, based in the home and community.Design Qualitative interview-based study of past users (n=76) of a family-based multicomponent healthy lifestyle programme in a mixed urban–rural region of New Zealand. Semistructured, home-based interviews were conducted and thematically analysed with peer debriefing for validity.Participants Families were selected through stratified random sampling to include a range of levels of engagement, including those who declined their referral, with equal numbers of interviews with Indigenous and non-Indigenous families.Results Three interactive and compounding determinants were identified as influencing engagement in Whānau Pakari: acute and chronic life stressors, societal norms of weight and body size and historical experiences of healthcare. These determinants were present across societal, system and healthcare service levels. A negative referral experience to Whānau Pakari often resulted in participants declining further input or disengaging from the programme. A fourth domain, respectful and compassionate healthcare, was identified as a mitigator of these three themes, facilitating participant engagement despite previous negative experiences.Conclusions While participant engagement in healthy lifestyle programmes is affected by determinants which appear to operate outside immediate service provision, the programme is an opportunity to acknowledge past instances of stigma and the wider challenges of healthy lifestyle change. The experience of the referral to Whānau Pakari is important for setting the scene for future engagement in the programme. Respectful, compassionate care is critical to enhanced retention in multidisciplinary healthy lifestyle programmes and ongoing engagement in healthcare services overall.